Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1158/1541-7786.mcr-19-0451
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Shifts Breast Tumor Microbiota Populations to Regulate Drug Responsiveness and the Development of Metastasis

Abstract: Breast tumors have their own specific microbiota, distinct from normal mammary gland tissue. Patients with breast cancer that present with locally advanced disease often undergo neoadjuvant chemotherapy to reduce tumor size prior to surgery to allow breast conservation or limit axillary lymph node dissection. The purpose of our study was to evaluate whether neoadjuvant chemotherapy modulates the tumor microbiome and the potential impact of microbes on breast cancer signaling. Using snap-frozen aseptically coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 29 publications
(44 reference statements)
1
76
0
1
Order By: Relevance
“…in breast tumor tissue as well as a bacterial diversity reduction. In this study, they also showed that non-treated patients had a lower abundance of Prevotella in tumor tissue [ 36 ]. On top of that, a study employing an HR+ BC mice model identified commensal dysbiosis as a host-intrinsic factor associated with metastatic dissemination.…”
Section: Microbiota Anti-cancer Therapy and Disease Progressionmentioning
confidence: 83%
“…in breast tumor tissue as well as a bacterial diversity reduction. In this study, they also showed that non-treated patients had a lower abundance of Prevotella in tumor tissue [ 36 ]. On top of that, a study employing an HR+ BC mice model identified commensal dysbiosis as a host-intrinsic factor associated with metastatic dissemination.…”
Section: Microbiota Anti-cancer Therapy and Disease Progressionmentioning
confidence: 83%
“…Previously we showed that bacterial tryptophan metabolism is suppressed in early stages of breast cancer, releasing the brake on breast cancer cells [ 16 , 17 , 40 ]. In that sense, IS behaves similar to other cytostatic metabolites [ 16 , 17 , 25 , 32 , 39 , 40 , 41 , 42 , 43 , 45 , 46 ]. Of note, in addition to the loss of cytostatic properties, the breast cancer oncobiome has an increased capacity for reactive estrogens and increase estrogen enterohepatic circulation [ 1 , 93 ].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, oncobiosis supports epithelial-to-mesenchymal transition (EMT) [ 16 , 17 , 40 , 44 ], migration and invasion [ 17 , 40 ], the reduction of oxidative stress [ 40 , 45 ], the proportions of ALDH1+ cancer stem cells [ 17 , 40 ], and widespread metabolic alterations [ 16 , 17 , 40 ] in cancers cells. These elementary steps are translated into enhanced tumor growth [ 16 , 17 ], aggressive tumor infiltration to the surrounding tissues [ 16 , 17 ], and enhanced metastasis formation [ 16 , 17 , 41 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent microbial analysis of breast tumors from untreated or neoadjuvant chemotherapy-treated patients showed chemotherapy-induced shifts in breast tumor microbiome with a significant increase in Pseudomonas spp. Moreover, the elevated abundance of Brevundimonas and Staphylococcus in patients' primary tumors was shown to be associated with the development of distant metastasis [78].…”
Section: Gut Microbiome Chemotherapy and Microbiota-modulated Efficmentioning
confidence: 99%